Phytochemical, Anti-diabetic and Cardiovascular Properties of Urtica dioica L. (Urticaceae): A Review - El Haouari, Mohammed; Rosado, Juan A. (Mini Reviews in Medicinal Chemistry, 2019)
Type 2 diabetes mellitus and cardiovascular diseases (CVD) have become the main cause of morbidity and death worldwide. In addition, current anti-diabetic and cardiovascular therapy is based on conventional drugs that have limited effectiveness and adverse side effects. In this regard, the role of medicinal herbs as a complementary or an alternative medicine is of great interest. Urtica dioica L. (Urticaceae), which is the focus of this review, has been widely used in traditional medicine to treat a variety of ailments, including, diabetes, hypertension and prostate cancer. The aim of this article is to review current knowledge related to the anti-diabetic and cardiovascular properties of U. dioica, with particular emphasis on the bioactive compounds, the plant parts used, and the action mechanism behind lowering blood glucose level and reducing risk of CVD. We also discuss the chemical composition and toxicological properties of the plant. From this review, it was suggested that the anti-diabetic and the cardiovascular effects of U. dioica are attributed to different classes of compounds, such as polyphenols, triterpens, sterols, flavonoids, and lectin which reduce the blood glucose level and the risk of CVD by their antihypertensive, antioxidant and anti-inflammatory properties and/or by interfering with different cellular signalization pathways, including increase of NO, inhibition of α-amylase and α-glycosidase, modulation of GLUT4 and protection of pancreatic β-cells, among others. The identification of the plant constituents and the understanding of their exact action mechanisms are necessary to prove the efficacy of the plant and develop it as pharmacological drug.
Keywords: toxicity